Chorordin-like 1 inhibits pancreatic cancer cell migration and invasion: involvement of the BMP4/SMAD pathway - Li, Wei; Zhong, Yalan; Song, Yuqiao; Wang, Hongmei; Jiang, Zheng (Frontiers in Oncology, 2025)
IntroductionPancreatic cancer is a highly aggressive malignancy with a 6% five-year survival rate. CHRDL1, a BMP4 antagonist, has tumor-suppressive effects in breast and gastric cancers, but its role in pancreatic cancer is unclear. This study explores CHRDL1’s function and mechanism in pancreatic cancer.MethodsStably transfected pancreatic cancer cell lines (PANC-1, SW1990) with lentivirus-mediated CHRDL1 overexpression were established to assess effects on cell proliferation, migration, and adhesion. Recombinant BMP4 treatment validated CHRDL1’s antagonism. Additionally, the TCGA database, immunohistochemistry, and RT-qPCR in both cell lines and patient tissues confirmed CHRDL1 expression. In vivo experiments were also conducted to observe the effect of CHRDL1 overexpression on pulmonary metastases.ResultsCHRDL1 was downregulated in pancreatic cancer, correlating with poor prognosis. Overexpression inhibited cell migration and adhesion (without affecting proliferation), reduced SMAD1/5/9 phosphorylation and RUNX2 expression, and counteracted BMP4-induced malignant behaviors.DiscussionCHRDL1 exerts tumor-suppressive effects in pancreatic cancer by inhibiting the BMP4/SMAD pathway, reducing migration, invasion, and metastasis. These findings clarify CHRDL1’s role, enhance understanding of pancreatic cancer mechanisms, and may offer diagnostic and therapeutic targets.